Applicability of Soybean Crude Urease-Calcite Precipitation Method in Various Liquefiable Sandy Soils - Akbar Renaldi Loebis; Heriansyah Putra (Indonesian Geotechnical Journal, 2023)
Liquefaction is a process in which pore-water pressure generated in the soil, usually by earthquake, is equal or almost equal to the total stress in the soil. This process reduces the effective stress to zero or near-zero, leading to reduction in shear strength and stiffness of soil. Hence, when liquefaction occurs, structures above and within the liquified soil, buildings, bridges, tunnels, docks, underground pipelines, and many other structures can get damaged. Soils which are susceptible to liquefaction are granular soil such as sand and silt. One of the methods that can be adopted to prevent liquefaction is soybean crude urease-calcite precipitation. This method uses urease enzyme in soybean crude as a biocatalyst to hydrolyze urea to produce carbonate ions and ammonium ions. In the presence of calcium ions, the carbonate ions react to produce calcium carbonate (calcite) precipitate. This research investigates the applicability of soybean crude urease-calcite precipitation method to improve various liquefiable sandy soil (fine, medium, coarse sand) at different relative density (40-60%). The soil strength after improvement was evaluated by using unconfined compressive strength (UCS) test, while calcite content was measured using acid leaching method. The results of the UCS test and calcite content analysis varies depending on the type of sand and relative density. The UCS value obtained from medium sand is higher than 50 kPa, potentially sufficient to prevent liquefaction. However, treatment on coarse sand failed to develop UCS, whereas treatment on fine sand produces limited UCS (< 10 kPa).